Epoxy-functionalized polysiloxane/Nano-SiO2 synergistic reinforcement in cryogenic mechanical properties of epoxy and carbon fiber reinforced epoxy laminate. (29th September 2020) - Li, Shichao; Chen, Duo; Gao, Chang; Yuan, Yuhuan; Wang, Hongyu; Liu, Xin; Hu, Bozhao; Ma, Jiwen; Liu, Minjing; Wu, Zhanjun
Abstract: Resin matrix of carbon fiber (CF) reinforced resin laminates play a key role in transferring the external stress to carbon fibers. Especially in cryogenic environment, the mechanical properties of CF reinforced resin laminates depend largely on the mechanical properties of resin matrix. In this work, an epoxy-functional polysiloxane/Nano-SiO2 (EFPS/Nano-SiO2 ) was prepared to enhance the mechanical properties of epoxy resin and carbon fiber reinforced epoxy laminate at RT and cryogenic environment. The TEM images indicate that the grafting of flexible macromolecule EFPS on the surface of Nano-SiO2 can improve the dispersion of Nano-SiO2 in epoxy resin. The tensile strength of epoxy resin with 5 wt% content of EFPS/Nano-SiO2 increases by 7.95% at RT and 17.07% at 90K, fracture strain by 54.55% at RT and 26.91% at 90K, fracture toughness (KIC ) by 48.82% at RT and 33.33% at 77K compared with the neat epoxy resin. The enhancement mechanism should mainly be attributed to the fact that the Nano-SiO2 particles debonding enhance the energy dissipation at crack front and the flexible EFPS significantly improves the movability of epoxy curing networks. The tensile strength of CF reinforced EFPS/Nano-SiO2 epoxy laminate shows an increase of 16.64% at RT and 25.01% at 90K, confirming that the effect of EFPS/Nano-SiO2 epoxy resin transferring the external stress from resin matrix to CF is better than that of neat epoxy resin. In addition, the mechanism of thermal cycling affecting the tensile properties of CF reinforced epoxy laminates are analyzed in detail. Graphical abstract: Image 1 Highlights: An epoxy-functionalized polysiloxane/Nano-SiO2 was prepared by simple co-hydrolytic condensation reaction. The grafting of EFPS on the surface of Nano-SiO2 can improve the dispersion of Nano-SiO2 in epoxy resin. The EFPS and Nano-SiO2 can synergistically enhance the mechanical properties of epoxy and composite laminate. Thermal cycling can affect the tensile properties of composite laminates.